Orthostatic hypo‐ and hyper‐tension are associated with cognitive decline: the S.AGES cohort. (20th December 2022) - Strumia, Mathilde; Vidal, Jean‐Sebastien; Hanon, Olivier; Rouch, Laure
Abstract: Background: The association between orthostatic hypotension (OHYPO) and cognition has reported conflicting results. Although orthostatic hypertension (OHYPER) is an emerging cardiovascular risk factor, only very few studies investigated its association with cognition. We aimed to assess the impact of OHYPO and OHYPER on cognitive performances in non‐institutionalized subjects aged ≥ 65 years. Method: The S.AGES (Sujets Âgés) cohort followed for three years non‐institutionalized subjects aged ≥ 65 years without major neurocognitive impairment at inclusion. OHYPO was defined as a decrease in systolic blood pressure (SBP) of at least 20 mmHg and/or diastolic blood pressure (DBP) of at least 10 mmHg from a sitting to a standing position. In contrast, OHYPER was defined as an increase in SBP of at least 20 mmHg and/or DBP of at least 10 mmHg under the same measurement conditions. Cognition was assessed using the Mini‐Mental State Examination (MMSE). Linear mixed models were used for the analyses. Result: We included 3, 170 subjects (mean age 78 years, 56% women). 209 (6.5%) had OHYPO at inclusion and 226 (7.1%) had OHYPER. Over time, MMSE was on average 0.5 points lower in patients with OHYPO compared to those without OHYPO or OHYPER (adjusted β [IC95%] = ‐0.52 [‐0.97; ‐0.08], p = 0.021) after adjustment for age, sex, education, baseline body mass index, smoking, alcohol intake, atrial fibrillation, congestive heart failure, transient ischemic attack or stroke, coronary artery disease, type 2 diabetes, dyslipidemia, seated SBP/DBP and antihypertensive treatment. Similarly, patients with OHYPER had, on average, poorer cognitive performances over time compared to those without pathological blood pressure (BP) postural changes (adjusted β [IC95%] = ‐0.54 [‐0.98; ‐0.09], p = 0.017). Conclusion: Both OHYPO and OHYPER were associated with cognitive decline. Considering that BP postural changes are common in the elderly and easy to detect, orthostatic BP measurements could help identify patients with greater risk of cognitive impairment.